Importance of the Quality Control of Herbal Teas: Evaluation of Two Senna Leaf Tisanes Brands Commercialized in Costa Rica through Physicochemical and Microbiological Assays Stipulated in the Central American Technical Regulation 11.03.56.09 - Mora Román, Juan José (2018)
The senna leaf contains a powerful natural laxative called anthraquinone. Despite this indication, the quality control of this raw material is not strict, compared to other substances with pharmacological properties, which is unacceptable. Therefore, the present investigation sought to evaluate physicochemical and microbiological quality aspects of the senna leaf tisanes from two brands commercialized in Costa Rica, through various assays established in the current Central American Technical Regulation (RTCA) 11.03.56.09. The aforementioned was made in order to identify and compare whether these aspects are constant or not for the different batches of the same product for each of the brands. For that reason, the following assays were done for three batches of two different brands: Labeling, minimum fill, organoleptic, foreign organic matter, identification, loss on drying, total ash, acid-insoluble ash, microbial enumerations and determination of specific microorganisms. The results show that the batches of both brands are in compliance for all the assays, except for the labeling assay (six of the 23 items required for primary and secondary packaging labeling were not found). For all of the above, the raw material commercialized in Costa Rica meet the quality standards according with the requirements of the RTCA. Also, there is reproducibility for the characteristics of the senna leaf between the different batches in each one of the two commercialized brands. This is an indication that the raw material used maintains the quality characteristics required to favor its efficiency and safety.